Analysis of Fish Cultivation Business in Cages in Tering Sub-District, Kutai Barat Regency East Kalimantan Province - Ramadana, Muhammad Andhika; Helminuddin, Helminuddin; Fahrizal, Wahyu (Faculty of Fisheries and Marine Science, Mulawarman University, 2023)
The purpose of this study was to determine the business analysis of goldfish cultivation in cages in Tering District using the Revenue Cost Ratio, Return on Investment, and Payback Period methods. This research was conducted from July to September 2022. The types of data in this research are primary data and secondary data with the data collection method using a questionnaire. The results showed that the RCR value was 1.48, ROI was 13,62%, and the payback period was 0,62. The results of business analysis research show that cultivating carp in cages is profitable.